Study On The Population Biology Of Soldier Catfish (Osteogeneiosus Militaris, Linnaeus 1758) In The Coastal Area Of Penang. - Jantan, Radziah (2014)
A study on population biology of marine catfish of the family Ariidae, Osteogeneiosus militaris was conducted from Pulau Betong in southwestern part of Penang. The study was conducted from February 2009 to August 2010. This study includes the biological aspects such as length-weight relationship (LWR), relative condition factor (Kn), feeding habits, reproductive biology and growth determination. The LWR equation obtained for female, male and immature O. militaris were W=0.01L3.095; W=0.027L2.763 and W=0.013L2.975, respectively. The value of Kn is more than 1 showing that O. militaris in Pulau Betong were having a good body condition. Analyses of the gastro-intestinal tract length shows that O. militaris having omnivorous feeding habits (GIT=1.62). The food items found in the stomach of O. militaris comprised of, panaeids, ophiurids, holothuroids, Setipinna spp., bivalves, brachyurans crab, fish skeleton, nematode, fish eggs, isopoda, fish otolith and unidentified organism. Result from the reproductive biology shows that the spawning period for O.militaris occurred throughout the year. However, spawning peak for this species were detected in June - July 2009 and December - February 2010. Length at first maturity for population of O. militaris in Pulau Betong is at 25.5 cm SL.